O MST e a edificação de uma proposta de reforma agrária baseada em princípios agroecológicos - Borsatto, Ricardo Serra; Carmo, Maristela Simoes do [UNESP] (My University, 2013)
In recent years, various social movements around the world have internalized new values and epistemological principles built upon environmental sustainability and social equity. Within this context, the aim of this paper was to understand the process of adopting a discourse based on the Agroecology by the Movement of Landless Rural Workers (MST) in Brazil. For this purpose, documents produced by MST were analyzed and semi-structured interviews with leaders of the Movement were applied. The results of the research allow us to state that the MST changed its discourse in relation to the production system to be adopted by its members, currently defending the adoption of agroecological principles. Even so, it is possible to observe that this change in posture has also presented limited effects in the transformation of the productive systems of settlements, and significant barriers still need to be overcome.

Nos últimos anos diferentes movimentos sociais ao redor do mundo têm internalizado em seus ideários novos valores e princípios epistemológicos edificados sobre as bases da sustentabilidade ambiental e equidade social. Dentro desse contexto, esse artigo objetivou compreender o processo de adoção de um discurso baseado na Agroecologia pelo Movimento dos Trabalhadores Rurais Sem Terra (MST) no Brasil. Para tanto foram analisados os documentos produzidos pelo MST e realizadas entrevistas semiestruturadas com lideranças do Movimento. Por meio da pesquisa empreendida é possível afirmar que o MST modificou o seu discurso em relação ao sistema de produção a ser adotado por seus militantes, defendendo atualmente a adoção de princípios agroecológicos. Porém, percebe-se que essa modificação de postura ainda tem apresentado efeitos limitados na transformação dos sistemas produtivos dos assentamentos e importantes entraves ainda terão que ser superados.
Keywords: Agroecology; Settlements; Peasant movements; MST; Land reform; Agroecologia; Assentamentos rurais; Movimentos camponeses; MST; Reforma agrária